Uncovering influence through Social Network Analysis: the role of schools in Education for Sustainable Development. Issue 3 (3rd May 2016) - Kolleck, Nina
Abstract: This paper examines the implementation of Education for Sustainable Development (ESD) in Germany and explores the possibilities of Social Network Analysis (SNA) for uncovering influential actors in educational policy innovation processes. From the theoretical perspective, an actor's influence is inferred from its relative position within issue-specific information flows and the trust placed in its capacities and expertise, instead of relying on an actor's openly expressed role and policy preferences. Drawing on techniques from quantitative SNA enables to analyse the social interactions as well as the frequency and type of information exchange amongst actors in a particular issue area. Empirically, I focus my attention on the educational innovation of ESD, which has been initiated at the global level, but is mainly put into practice at the national or regional level. Data for the study come from mixed mode interviews with a standardised questionnaire. The interviews were conducted and analysed using egocentric and complete SNA. I find, amongst others results, that NGOs and governmental actors occupy significantly more central, prestigious and influential network positions than schools in the course of implementing ESD in Germany. Furthermore, school representatives exhibit few and weak relations, and mostly share links with other formal education actors.